Effective solutions to pollution mitigation for public welfare - Gezerman, Ahmet Ozan, 1978-; Corbacioglu, Burcu Didem, 1967-; Gurjar, Bhola R., 1965- (Engineering Science Reference, 2018)
"This book developed a solution for industrial problems that endanger public welfare. It explores the importance of cost-effective solutions for treatment, emission abatement, and other removal methods need to be developed"--